Pengaruh Self-Assessment Good Corporate Governance dan Non-Performing Loan (NPL) terhadap Return on Assets (ROA): Studi Kasus pada Bank BUMN yang Terdaftar di Bursa Efek Indonesia Tahun 2020–2023 - Janah, Tata Mifthakul; Rahmawati, Ita (ARZUSIN, 2025)
The issue of profitability in state-owned bank (BUMN) remains a primary concern, especially in relation to the effectiveness of implementing Good Corporate Governance (GCG) and managing problematic loans or Non-Performing Loans (NPL). This study aims to analyze the effect of GCG and NPL on Return on Assets (ROA) in the banking subsector of BUMN listed on the Indonesia Stock Exchange during the 2020–2023 period. The method used is an associative quantitative approach with purposive sampling technique, resulting in 4 out of 6 BUMN banks as the sample. Analysis was conducted using panel data regression with E-Views 12. The results indicate that, partially, GCG does not have a significant effect on ROA, while NPL has a significant negative effect on ROA. Simultaneously, GCG and NPL have a significant effect on ROA, with an Adjusted R-Squared value of 0.73, which means that 73% of the variation in ROA can be explained by these two variables. The conclusion of this study is that good credit risk management, particularly in reducing the NPL ratio, has a greater influence on profitability compared to the separate implementation of GCG. The practical implication of this research is the importance of integrating good corporate governance with risk management strategies to improve asset efficiency and sustainable financial performance in the BUMN banking sector.